2014
DOI: 10.1002/pro.2543
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution crystal structures of the photoreceptor glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) with three and four‐bound NAD molecules

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) catalyzes the oxidative phosphorylation of D-glyceraldehyde 3-phosphate (G3P) into 1,3-diphosphoglycerate (BGP) in the presence of the NAD cofactor. GAPDH is an important drug target because of its central role in glycolysis, and nonglycolytic processes such as nuclear RNA transport, DNA replication/repair, membrane fusion and cellular apoptosis. Recent studies found that GAPDH participates in the development of diabetic retinopathy and its progression after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…The structures of GAPDH from archaea, bacteria, and eukaryotes have been determined by x‐ray crystallography, and show that the NAD + cofactor is bound, despite not being added during protein purification. In mammalian GAPDH structures, two, three, or even four NAD + molecules have been observed per homotetramer. In addition, we recently showed that GAPDH was present as a mixture of NAD + ‐bound and NAD + ‐free species in solution by nano‐ESI/MS/MS studies .…”
Section: Structural Determinants Of Gapdhmentioning
confidence: 99%
“…The structures of GAPDH from archaea, bacteria, and eukaryotes have been determined by x‐ray crystallography, and show that the NAD + cofactor is bound, despite not being added during protein purification. In mammalian GAPDH structures, two, three, or even four NAD + molecules have been observed per homotetramer. In addition, we recently showed that GAPDH was present as a mixture of NAD + ‐bound and NAD + ‐free species in solution by nano‐ESI/MS/MS studies .…”
Section: Structural Determinants Of Gapdhmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an enzyme that catalyses the conversion of glyceraldehyde 3-phosphate to 1,3-bisphosphoglycerate using NAD + as a cofactor (Baker et al, 2014) and is known to be a moonlighting protein (Savreux-Lenglet et al, 2015). This enzyme plays multiple roles in the regulation of mRNA stability (Zhou et al, 2008), intracellular membrane trafficking (Sirover, 2012), iron uptake and transport (Zaid et al, 2009), DNA replication and repair (Zheng et al, 2003), and nuclear RNA transport (Dastoor & Dreyer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Unit cell dimensions were a = 79.8 Å, b = 126.5 Å, c = 83.8 Å; α = 90°, β = 118°, γ =90°. Although bovine GAPDH existed as a homotetramer identical to known structures in this protein family, it had three NAD molecules bound instead of either two or four found in other mammalian GAPDHs, a feature that distinguishes it from others PDB entries, 1J0X (Cowan-Jacob, Kaufmann, Anselmo, Stark, & Grutter, 2003), 1U8F (Jenkins & Tanner, 2006), and 1ZNQ (Baker, Shi, Wang, & Palczewski, 2014). …”
Section: Pilot Experimental Resultsmentioning
confidence: 90%